Three-phase tri-state integrated boost inverter with special space vector and dq0 control - De Brito, Moacyr A.G. [UNESP]; Junior, Luigi G. [UNESP]; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
This paper presents a three-phase integrated inverter suitable for stand-alone and grid-connected applications. Furthermore, the utilization of the special features of the tri-state coupled with the new space vector modulation allows the converter to present an attractive degree of freedom for the designing of the controllers. Additionally, the control is derived through dq0 transformation, all the system is described and interesting simulation results are available to confirm the proposal. © 2012 IEEE.
Keywords: New Space Vector Modulation; Stand-Alone and Grid Connected PV applications; Three-phase Integrated Inverter; Boost inverters; Degree of freedom; Dq0 transformation; Grid-connected; Grid-connected PV; Integrated inverter; Space Vector; Space Vector Modulation; Electric inverters; Modulation; Power electronics; Vector spaces